English for Daily Activities: Textbook Developed for Islamic Education Study Program at STAIN Mandailing Natal - Fitriani, Fitriani; Defi, Wahyu Fitrina; Pratami, Fuji (CV. Creative Tugu Pena, 2023)
This research project aims to create teaching materials in the form of textbooks specifically designed for English courses, focusing on